SEPARATION OF THE COMPETITION OF CRIMINAL LAW NORMS AND THE CONCEPTUAL AGGREGATION OF CRIMINAL OFFENCES - Krastiņš, Uldis (Administrative and Criminal Justice, 2016)
The article analyses two independent Criminal law institutes – competition of criminal law norms and conceptual aggregation of criminal offences, which mutually excludes each other in the same offence and has their own legal validity in qualification of the offence. In case of competition, the offence should be qualified according to one of the competing standards, but conceptual aggregation of criminal offences – according to two or more norms of the criminal law.